A human capital theory of who escapes the grasp of the local monopsonist - Matthew E. Kahn; Joseph S. Tracy (American Enterprise Institute (AEI), 2024)
Over the last thirty years, there have been significant changes in several empirical measures of local labor market monopsony power. A monopsonist has a profit incentive to offer lower wages to local workers. High skilled mobile workers can avoid these lower wages by moving to other more competitive local labor markets. We explore several empirical implications of a Roy Model of heterogeneous worker sorting across local labor markets. Counties with concentrated labor markets are predicted to experience a "brain drain" over time. Using data over four decades we document this deskilling and loss of high-income workers associated with local monopsony power. An implication is that labor market competition complements product market competition to foster faster city growth. Going forward the rise of work from home may act as a substitute for migration by high-skill workers from monopsony markets.
Keywords: 330; Regionaler Arbeitsmarkt; Arbeitsmarktsegmentation; Monopson; Lohnniveau; Hochqualifizierte Arbeitskräfte; Ungelernte Arbeitskräfte; Brain Drain; Arbeitsmarkttheorie